New Approach in Interreligious Dialogue Sought - Ridwan Ridwan (Universitas Islam Internasional Indonesia (UIII), 2025)
Rethinking Interreligious Dialogue: Orality, Collective Memory, and Christian-Muslim Engagements in Indonesia by Izak Y.M. Lattu (Leiden, the Netherlands: Brill, 2023) This important book, published in 2023, explores interreligious conflict in Maluku, particularly in Ambon City, between 1999 and 2004, involving Muslims and Christians. What started as a trivial dispute between two young men of different religions and ethnicities (one a Muslim Bugis migrant and the other a Christian Malukan local) escalated into a deadly conflict. The conflict intensified, resulting in thousands of casualties and displacing around one million people in the region, alongside the destruction of 80 percent of infrastructure. As a result, the conflict in Ambon is intractable, with a history of past domination and inequitable conditions, changes in domination, and a complex mixture of economic, political, and cultural issues (Coleman, 2006).